Contra la moral i las buenas costumbres - Edwin Monsalvo; Roberto González Arana (Caravelle)
This paper analyzes the judicial proceedings of first instance in cases of vagrancy led by the Mayors and Judges Parochial Manizales during the first two decades of existence of this border region of Antioquia authority. The aim is to show the state attempts to control a population through sanctions, penalties and fines imposed on violators of police. Our hypothesis is to show that the summaries were prosecuted how officials attempted to correct behavior that they considered immoral and educate them in a pedagogy of work that eliminated activity and vice.